2020
DOI: 10.3390/ijms21144876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auxin (IAA) on the Fast Vacuolar (FV) Channels in Red Beet (Beta vulgaris L.) Taproot Vacuoles

Abstract: In contrast to the well-studied effect of auxin on the plasma membrane K+ channel activity, little is known about the role of this hormone in regulating the vacuolar K+ channels. Here, the patch-clamp technique was used to investigate the effect of auxin (IAA) on the fast-activating vacuolar (FV) channels. It was found that the macroscopic currents displayed instantaneous currents, which at the positive potentials were about three-fold greater compared to the one at the negative potentials. When auxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Vacuoles are not only the largest organelles of mature plant cells, they also play pivotal roles in plant growth and development, notably through the regulation of turgor pressure. This might involve vacuole acidification through the V-ATPase, downstream of auxin signaling [ 45 , 46 ]. To investigate the putative contribution of V-ATPase-dependent vacuole acidification on fugu5 CCE, we analyzed the vha-a2 vha-a3 fugu5–1 triple mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vacuoles are not only the largest organelles of mature plant cells, they also play pivotal roles in plant growth and development, notably through the regulation of turgor pressure. This might involve vacuole acidification through the V-ATPase, downstream of auxin signaling [ 45 , 46 ]. To investigate the putative contribution of V-ATPase-dependent vacuole acidification on fugu5 CCE, we analyzed the vha-a2 vha-a3 fugu5–1 triple mutant.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has been reported that plant vacuoles significantly increase their volume (ca. two-fold) upon incubation with 1 μM IAA [ 45 , 46 ], linking auxin and vacuolar acidification, and providing insights into vacuole volume regulation during post-mitotic plant cell expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that apart from the posttranslational, auxin-dependent up-regulation of both the K + uptake channels and the PM H + -ATPases, auxin also regulates their expression [ 28 , 31 ]. Quite recently, it was also shown that the SV (slow vacuolar) and FV (fast vacuolar) channels, which represent the conductance of the major cations across the tonoplast, are involved in the IAA-induced volume changes of the vacuoles [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The patch-clamp experiments that were recently performed by Burdach et al [ 27 , 28 ] should also be mentioned. These authors showed that the SV (slow vacuolar) and FV (fast vacuolar) channels, which represent the conductance of the major cations across the tonoplast, are involved in the IAA-induced volume changes of the vacuoles.…”
Section: Introductionmentioning
confidence: 99%